Isolation and Molecular Identification of Proteolytic Bacteria from Rusip an Indonesian Fermented Food - Amatullah, Lutfiana Hary; Afifah, Diana Nur; Jannah, Siti Nur (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Processing fish with the fermentation method can increase the nutritional content, bring out a distinctive taste, and make the fish last longer. Rusip is a type of complementary food from Bangka Belitung in the form of fish sauce that has been rotten or fermented. Rusip is made from fermented anchovy (Clupeoides borneensis). The concept of fermentation in Rusip is the breakdown of complex protein molecules by proteolytic bacteria into simple amino acid components.The purpose of this study was to determine the presence of proteolytic bacteria that play a role in rusip fermentation.The media used in screening proteolytic bacteria is skim milk agar (SMA) media. Then it was incubated at 37oCfor 24 hours. Bacterial colonies that form a clear zone on the media indicate that these bacteria can degrade protein. After the isolation process and isolates were obtained, the bacteria were characterized by Gram staining method and molecular identification.The results showed that there were proteolytic bacteria in Rusip food, and the 3 best isolates that produced protease enzymes were identified as Bacillus cereus.